Analisis Pengaruh Suku Bunga Kredit, Tingkat Inflasi dan Kurs Valuta Asing Terhadap Ekspor Kerajinan Kerang Provinsi Bali Tahun 1996-2014 - Samaranatha, Komang Gede; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
Exports are the most profitable activity can increase due to foreign exchange of a country, such as the activity of export of handicrafts in the province of Bali. Bali has a lot of shells that can be used  a variety of accessories or jewelry. The purpose of this study to determine the effect of mortgage interest rates, inflation rates, foreign exchange rates against the volume of export of handicrafts shellfish Bali Province of the 1996-2014. This study are using secondary data. Data processed by multiple linear regression analysis. The results showed that the partial loan interest rates have significant negative effect on exports craft shells, partially inflation rate did not significantly affect the export of handicrafts shellfish, and partially in foreign exchange rates have not significant effect on the export of handicrafts shellfish.
Keywords: Interest Rates; Inflation; Foreign Exchange